Modified-TAM Analysis of the Implementation of the e-Hospital System on Polyclinic Service - Pratama, Devina Gracia; Prasetyo Agung, Ignatius Wiseto; Purwadhi, Purwadhi (Journal of Health Policy and Management, 2022)
Background: Technology in the field of health services allows an individual to get a productive life and a longer life expectancy. The purpose of this study was to provide describe of obstacles in the implementation of the e-Hospital system, especially EMR services at the Dermatology & Venereology (DV) Polyclinic "X" Hospital from the perspective of service providers.Subjects and Method: This qualitative descriptive research was done with natural observation and using electronic questionnaire based on Modified-TAM Analyses. It was conducted since February-June 2022. The study participants were determined based on the Non-Random Purposive Sampling technique which included all of DV Polyclinic staff at “X” Hospital (3 doctors, 2 nurses, and 2 administrative staff).Results According to the results, it was found that the implementation of the e-Hospital system at the DV Polyclinic was still not running optimally. The most commonly encountered barrier factors based on the Perceived Usefulness (PU), Perceived Ease of Use (PEOU), and Behavioural Intetion (BEI) components was the perception that “e-Hospital cannot replace the conventional system” (50%); and for the PTH & SI components was “the hospitals are not ready to run e-Hospital system” (60%).Conclusion: The hospital management needed to re-evaluate which constraint factors cause these perspectives, which could be an obstacle in implementing the e-Hospital system. In addition, it was necessary to re-emphasize the e-Hospital system and its benefits through periodically training, affirm the vision and mission related to the system, and do periodic feedback evaluations from service providers so that the hospital management could comprehend which obstacles were found and were able to make changes and increase the motivation of service providers to use the e-Hospital system.Keywords: e-Hospital System, Polyclinic Services, Service Provider, TAMCorrespondence: Devina Gracia Pratama. Master of Management Postgraduate Program, Adhirajasa Reswara Sanjaya University. Terusan Sekolah st. No.1-2, Cicaheum, Kec. Kiaracondong, Kota Bandung 40282, West Java. Email: devinagracia07@gmail.com. Mobile: +6281220811014.Journal of Health Policy and Management (2022), 07(03): 218-226https://doi.org/10.26911/thejhpm.2022.07.03.06